LANGUAGE, DISCRIMINATION AND DISABILITY IN THE SCHOOL SETTING OF MAGELLAN EDUCATION. A HUMAN RIGHTS-BASED APPROACH FROM OCCUPATIONAL THERAPY - Yupanqui Concha, Andrea; Gonzalez, Maria A.; Llancalahuen, Miguel; Quilodran, Walter; Toledo, Carla (My University, 2016)
This article puts emphasis on the discriminatory language used today to the person with disabilities, specifically in the school context. Several authors have examined how the communicative interaction, through the language, can creates realities, shapes identities and to the social world, contributing to the abuse of power and domination. It opens a spectrum of discriminatory possibilities towards certain social minorities, which would incite their segregation and those elements are reproduced through the spaces of the school (Echeverria, 1994; Maturana, 1998; Van Dijk, 1996; 2003; Van Dijk & Bixio, 2009; Magendzo y Donoso, 2000; Barton, 2005; Fairclough, 2010). The objective of this study was to evaluate the impact of a process of awareness and training aimed at educational institutions on the issue of disability and inclusive language. The study used a mixed methods (combining qualitative and quantitative methods research) with an approach of Participative-Action Research, applied to four educational establishments in the city of Punta Arenas, Chile, which sample considered students, teachers and authorities. Community - participative techniques of intervention were used and the technical of compilation of information was semi-structured interview and survey. The results were analyzed using qualitative procedures of the Grounded Theory (Glaser & Strauss, 1967), and the quantitative analysis on a statistical descriptive correlation. In conclusion, this research indicates that a high percentage of discriminatory and non-inclusive language is used in schools of the region, which affects interpersonal relationships and school life, thus violating the human rights of children and young with disabilities. Occupational Therapy has the responsibility of eliminating the situations of occupational apartheid, promoting the occupational justice in those places where discrimination exists in all forms, by the modification of social barriers, to constructing a more inclusive society.
Keywords: language; discrimination; disability; human rights; education; occupational therapy